Effect of the Surface Treatment of Titanium on the Texture, Mechanical and Physicochemical Properties of the Rf-Magnetron Sputtered Silver-Doped Hydroxyapatite Coatings; XII International Conference on Nanostructured Materials (NANO 2014), July 13-18, 2014 Moscow, Russia - Pryamushko T. S. Tatiana Sergeevna; Grubova I. Yu. Irina Yurievna; Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna; Ivanova A. A. Anna Aleksandrovna; Kravchuk S. S. Sergey Sergeevich; Primak O. Oleg; Mattias E. Epple (Nanoceramics, 2014)
Title screen